INTEGRASI PENDIDIKAN ANTIKORUPSI KE DALAM PERKULIAH PENDIDIKAN AGAMA ISLAM BERBASIS KURIKULUM MERDEKA - Irianto (BEduManagers Journal : Borneo Educational Management and Research Journal, 2023)
For the Indonesian people, the issue of corruption is the most important part of the issue of values. This means that corruption must be prevented and eradicated to restore Indonesia's national values. One of the problems associated with the order of social values is the incessant corruption. Therefore, the research in this research journal is a descriptive qualitative research. Qualitative research is a research procedure that produces descriptive data from people and observed behavior in the form of written or spoken language. research conducted with qualitative methods subject and object Research was conducted on STTI Bontang students majoring in mechanical engineering and chemical engineering semester 2 and UIN Makassar students, using interviews data collection via google from c. Internal In teaching and learning interactions, students are the main key to successful learning, which takes place during the learning process. Both lecturers and students expect good results during the learning process, but in reality not all processes go as smoothly as expected. Various obstacles are encountered in the learning process, especially for lecturers of Islamic religion courses when implementing anti-corruption teaching materials that contain Islamic religion material. The way lecturers conduct anti-corruption education to students is inseparable from the various obstacles faced in the implementation of anti-corruption education. Anti-corruption education is the latest content of the independent curriculum and is one of the Islamic religion courses. As well as the factor of the Indonesian state itself whose corruption rate increases every year and the absence of a deterrent effect from the perpetrators of corruption is sad. d. External Barriers External External obstacles are the ability of students to understand learning material, namely how the lecturer chooses learning material that is not boring so that students can understand what is being conveyed. But in reality, even though the lecturer provides learning material as well as possible, it returns to the individual student. Suggestions Judging from the conclusion about the integration of anti-corruption education into Islamic religious lectures based on the independent curriculum, the suggestions that can be given are: Anti-corruption education is a very important subject, so anti-corruption education needs to be included in the education curriculum and taught to all students or specialists in higher education. However, this type of corruption can also be prevented by strengthening mutual trust because anti-corruption education alone is not enough, but there must also be legal efforts where everyone who commits and is proven to have committed a corruption crime must be punished in accordance with the applicable law. What needs to be done in learning anti-corruption education, or what has already been done but needs to be further implemented, is systematically shown in the educator program.